Ocular Manifestations of Neuronal Ceroid Lipofuscinoses. (3rd October 2021) - Singh, Rohan Bir; Gupta, Prakash; Kartik, Akash; Farooqui, Naba; Singhal, Sachi; Shergill, Sukhman; Singh, Kanwar Partap; Agarwal, Aniruddha
ABSTRACT: Neuronal ceroid lipofuscinoses (NCLs) are a group of rare neurodegenerative storage disorders associated with devastating visual prognosis, with an incidence of 1/1, 000, 000 in the United States and comparatively higher incidence in European countries. The pathophysiological mechanisms causing NCLs occur due to enzymatic or transmembrane defects in various sub-cellular organelles including lysosomes, endoplasmic reticulum, and cytoplasmic vesicles. NCLs are categorized into different types depending upon the underlying cause i.e., soluble lysosomal enzyme deficiencies or non-enzymatic deficiencies (functions of identified proteins), which are sub-divided based on an axial classification system. In this review, we have evaluated the current evidence in the literature and reported the incidence rates, underlying mechanisms and currently available management protocols for these rare set of neuroophthalmological disorders. Additionally, we also highlighted the potential therapies under development that can expand the treatment of these rare disorders beyond symptomatic relief.